Suicide - Fazel, S; Runeson, B (Massachusetts Medical Society, 2020)
Suicide accounts for approximately 1.5% of deaths per year worldwide. Risk factors are known for populations, and psychological models address individual risks; the models and tools for assessing suicide risk are imperfect but provide some guidance.